1997
DOI: 10.1055/s-0038-1656110
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden, C>T MTHFR Polymorphism and Genetic Susceptibility to Preeclampsia

Abstract: SummaryWe performed a case-controlled study to investigate whether the FV Leiden mutation and the C>T677 polymorphism of the 5,10 methylene tetrahydrofolate reductase (MTHFR) are associated with the occurrence of preeclampsia in 96 otherwise healthy preeclamptic women and 129 parous women as controls. FV Leiden carriers were 10 (10.5%) in cases and 3 (2.3%) in controls (OR: 4.9, 95% Cl: 1.3-18.3). MTHFR TT homozygotes were 28 (29.8%) in cases and 24 (18.6%) in the control group (OR: 1.8,95% Cl 1.0-3.5). No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
120
6
7

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(140 citation statements)
references
References 28 publications
7
120
6
7
Order By: Relevance
“…Maybe it is caused by population differences inside the country. 23,25 It seems to be clear from the previous studies and our studies that the prevalence of MTHFR C677T variant in pre-eclamptic patients does not differ from the healthy pregnant women. In these studies, the patient selection is well defined and the population is homogeneous.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Maybe it is caused by population differences inside the country. 23,25 It seems to be clear from the previous studies and our studies that the prevalence of MTHFR C677T variant in pre-eclamptic patients does not differ from the healthy pregnant women. In these studies, the patient selection is well defined and the population is homogeneous.…”
Section: Discussionsupporting
confidence: 52%
“…It was the same in O'Saughenessy et al's 21 publication where 283 samples were studied. A Mexican, an Italian and a Korean study concluded with similar findings, 21,22,24 even though these findings are in contradiction with Grandone et al 25 and Sohda et al's 26 results, where significant differences among these two groups were found. It is interesting, however, that even publications from the same country have contradictions in prevailing.…”
Section: Discussionmentioning
confidence: 69%
“…Notable among these are genetic predispositions toward thrombophilia, such as the FV-Leiden mutation, 33 leading to thrombosis because of anti-coagulant protein C resistance; the homozygous methylenetetrahydrofolate mutation, 33 resulting in hyperhomocysteinemia and a consequent thrombotic condition; the prothrombin G20210A mutation, 34 resulting in elevated plasma prothrombin concentrations and the associated risks of coagulopathies; and the vascular thrombotic dispositions of an anti-phospholipid syndrome. 35 Many of the early associations between thrombophilia and pregnancy loss were studied through retrospective analyses with small numbers of patients, thus tempering the conclusion as to whether causal relationships exist between complications of pregnancy and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…In 1997, two separate case-control studies independently reported a significant association between the TT genotype and preeclampsia (87,88) . Since then, numerous studies have investigated this association; however, conflicting results have emerged (Table 2).…”
Section: Role Of the Mthfr Genotype In Determining The Risk Of Hypertmentioning
confidence: 99%
“…Most recently, the meta-analysis by Xia et al (95) reported that the TT genotype compared with the CC and CT genotypes carried a significantly greater risk of preeclampsia (by 76%) among Asian women only, whereas in Caucasian women this increased risk was not evident. It is worth noting however that a much greater number of large-scale studies in this area have been conducted within Asian populations with far fewer studies conducted in Caucasian populations; a factor that limits Sohda et al (87) 425 Japan 2·5 (1·3, 4·8) Grandone et al (88) 225 Italy 1·8 (1·0, 3·5) Kupferminc (96) 144 Israel 2·9 (1·0, 8·5) Powers et al (97) 237 Caucasian women 1·28 (0·58, 2·79) Kobashi et al (98) 316 Japan 0·68 (0·30, 1·55) Laivuori et al (99) 216 Finland 0·50 (0·14, 1·77) Rigo et al (100) 221 Caucasian women 1·13 (0·38, 3·37) Morrison et al (101) 404 Scotland 1·00 (0·55, 1·82) Prasmusinto et al (102) 112 Germany and Croatia 0·28 (0·03, 2·47) Pegoraro et al (103) 609 South African (Black) 0·62 (0·06, 6·90) Perez-Mutul et al (91) 325 Mexico 0·94 (0·59, 1·49) Williams et al (104) 304 Peru 1·6 (0·7, 3·8) Yilmaz et al (105) 111 Turkey 0·84 (0·26, 2·67) Also-Rallo et al (79) 165 Spain 0·73 (0·31, 1·76) Hernandez-Diaz et al (86) 154 USA/Canada 3·0 (1·2, 7·7) Stiefel et al (106) 584 Spain 0·92 (0·50, 1·71) the extent to which different populations can be compared. An additional limitation is that genotype-driven recruitment is generally not undertaken in these studies, a feature that is reflected by the relatively small numbers of pregnant women with the TT genotype being investigated and these raised the concern that many such studies may be statistically underpowered.…”
Section: Role Of the Mthfr Genotype In Determining The Risk Of Hypertmentioning
confidence: 99%